Gertrudis Segovia: An Approach to her Figure (2022)
The main aim of this work is to raise awareness of the figure of Gertrudis Segovia, a Sevillian writer of the early 20th century. Her work had a notable impact, but throughout the years, it fell into oblivion, as happens with the legacy of many women writers. To bring her figure back, we propose to analyse the different sources from that period (especially journalistic ones, dedicated to her) and we will approach her poetic production mainly through her work Poesías (1911). An analysis of her verses allows us to establish the three fundamental axes around which her poetic universe revolves: family, patriotism and regionalism, and religion. The approach to her work involves highlighting the importance of her literary creation, which has been unjustly forgotten, and reconstructing part of the literary heritage of Andalusian women writers.